2017
DOI: 10.1002/erv.2502
|View full text |Cite
|
Sign up to set email alerts
|

Affective Responses in Different Stages of Anorexia Nervosa: Results from a Startle‐reflex Paradigm

Abstract: We observed diverging subjective and psychophysiological reactions in different stages of AN. Psychophysiological methods can help to attain a more comprehensive understanding of biological alterations in the long-term course of AN. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
5
16
0
Order By: Relevance
“…If this finding can be replicated in a larger sample, this would support the notion that reduced weight attenuates anxiety in AN (Kaye, ; Kaye et al, ). This finding is in line with and extends the previous finding by Erdur et al () who found a general flattening in emotion‐modulated startle response in acute and chronic but not in recovered patients with AN.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…If this finding can be replicated in a larger sample, this would support the notion that reduced weight attenuates anxiety in AN (Kaye, ; Kaye et al, ). This finding is in line with and extends the previous finding by Erdur et al () who found a general flattening in emotion‐modulated startle response in acute and chronic but not in recovered patients with AN.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of a blunted emotional reactivity to fear‐related material in AN are in line with previous findings of reduced amygdala activity in response to fear‐eliciting stimuli (Leppanen et al, ). Furthermore, the findings of the present study extend and differentiate previous findings of a lack of emotion‐modulation of the startle response to pleasant stimuli (Friederich et al, ) and a general lack of emotion‐modulation of startle response to both pleasant and unpleasant stimuli in AN (Erdur et al, ; Friederich et al, ), by showing a specifically reduced startle response to fear‐eliciting stimuli in a larger sample of patients with AN. The present finding is, however, in contrast to a previous study in adolescent patients with AN (Reichel et al, ) which did not find a blunted emotion‐modulation of startle response to negative emotional stimuli.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…2013;Shott et al, 2016;Tchanturia et al, 2012;Wagner et al, 2006;Yackobovitch-Gavan et al, 2009). However, in contrast, in a few studies, patients improved in psychological distress, depression, and anxiety, not differing significantly from healthy controls(Oldershaw et al, 2012;Harney, Fitzsimmons-Craft, Maldonado, & Bardone-Cone, 2014;Bernardoni et al, 2016;Bentz et al, 2017;Erdur, Weber, Zimmermann-Viehoff, Rose, & Deter, 2017) specifically when considered fully recovered(Harney et al, 2014).…”
mentioning
confidence: 98%